Chronic Effects of Neurotrauma Consortium (CENC) multicentre study interim analysis: Differences between participants with positive versus negative mild TBI histories. (29th July 2018) - Walker, William C.; Hirsch, Shawn; Carne, William; Nolen, Tracy; Cifu, David X.; Wilde, Elisabeth A.; Levin, Harvey S.; Brearly, Timothy W.; Eapen, Blessen C.; Williams, Rick
ABSTRACT: Objectives: Compare characteristics and outcomes of combat-exposed military personnel with positive versus negative mild traumatic brain injury (mTBI) histories. Setting: Recruitment was from registration lists and ambulatory clinics at four veterans administration hospitals. Participants: Consented veterans and service members completing initial evaluation by September 2016 ( n = 492). Design: Observational with cross-sectional analyses. Main measures: Multimodal assessments including structured interviews, record review, questionnaires, neuroendocrine labs and neurocognitive and sensorimotor performance. Results: In unadjusted comparisons to those absent lifetime mTBI, the mTBI positive group (84%) had greater combat exposure, more potential concussive events, less social support and more comorbidities, including asthma, sleeping problems and post-traumatic stress disorder. They also fared worse on all sensory and pain symptom scores and self-reported functional and global outcomes. They had poorer scores on Wechsler Adult Intelligence Scale-IV coding (processing speed), TMT-B (visual-motor integration and executive function) and two posturography subtests, but were otherwise equal to TBI negative participants on neurocognitive and sensorimotor testing and neuroendocrine levels. Conclusions: Although differences in characteristics exist which were not adjusted for, participants with historical mTBI have greater symptomatology and life functioning difficulties compared with non-TBI. Performance measures were less dissimilar between groups. These findings will guide further research within this accruing cohort.